Prevalence, immediate neonatal outcomes, and factors associated with short birth intervals among mothers delivered at Mubende Regional Referral Hospital, Uganda - Maryan, Ahmed Hassan; Elioba, John; Okello, Maxwell; Byaruhanga, Paul; Omar, Abdirizak Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Short birth intervals (SBIs) pose significant public health risks, particularly in low-resource settings like Uganda, where they are associated with adverse neonatal outcomes. Despite WHO recommendations for optimal birth spacing, high rates of SBIs persist, largely due to socio-economic, cultural, and healthcare access challenges. This study aimed to determine the prevalence, immediate neonatal outcomes, and associated factors of SBIs among mothers at Mubende Regional Referral Hospital. Methods: A cross-sectional study was conducted from May to August 2024, involving 422 postpartum mothers. Data on sociodemographic, obstetric, and behavioral factors were collected, and logistic regression analysis was used to identify factors associated with SBIs and assess the impact on neonatal outcomes, including small for gestational age, preterm birth, early neonatal death, and External congenital defects. Results: The study revealed an SBI prevalence of 40.3%. The most common adverse neonatal outcomes were Small for gestational age (31%), and preterm birth (26%). Key factors associated with SBIs included young maternal age (<20 years, aOR 2.18, 95% CI: 1.13-4.22), rural residence (aOR 2.84, 95% CI: 1.69-4.78), lack of antenatal care (aOR 4.64, 95% CI: 1.80-11.95), unplanned pregnancies (aOR 2.15, 95% CI: 1.35-3.41), and short breastfeeding duration (<12 months, aOR 3.26, 95% CI: 2.05-5.20). Conclusions: The study identified a high prevalence of SBIs, with significant associations to adverse neonatal outcomes such as Small for gestational age, and preterm birth. Factors contributing to SBIs included young maternal age, rural residence, limited antenatal care, and unplanned pregnancies, are highlighting the need for targeted family planning and maternal health interventions.